IDEOLOGIZATION OF EDUCATION SYSTEM IN THESOVIET PERIOD (1950-1980 years) (Scientific journal of the Fergana State University, 2023)
This article discusses the ideological policies and the consequences of the education system in Uzbekistan within the years of 1950 and 1980.